Cocoa price prediction in North Sumatra using Singular Spectrum Analysis (SSA) Algorithm - Fransiska, Sintia; Husein, Ismail (Politeknik Ganesha Medan, 2023)
The implementation of agricultural development is basically aimed at increasing the welfare of the people, especially farmers, providing a source of foreign exchange through exports, supplying food and industrial raw materials, alleviating poverty, providing employment and improving people's income. Cocoa is a leading commodity which is a source of income for farmers in North Sumatra. Price fluctuations sometimes make farmers suffer losses, so it is necessary to make a cocoa price prediction to anticipate future losses. This study aims to determine the prediction results of cocoa prices in North Sumatra in 2023 and the accuracy of the method used. The results of the study obtained the prediction of cocoa prices in North Sumatra Province in 2023 using the Singular Spectrum Analysis (SSA) method from January to December, respectively, Rp. 34876 in January, February prediction of Rp. 33967, March prediction of Rp. 33446, in April RP 33725, prediction in May of Rp. 33986, prediction in June of Rp 33916, in July Rp. 34196, predictionin August of Rp. 34841, prediction in September of Rp. 35228, in October of Rp. 3479, in November Rp 344517, the December prediction is Rp 34770 with a prediction accuracy level based on the standard MAPE value of 0.96%. The MAPE value obtained indicates that the SSA approach with Windows length 18 and 14 groups is very accurate for prediction cocoa price in North Sumatra Province because it is less than 10% and close to 0%.